Health Care Professionals’ compassion rounds : A pilot study - Lakatamitou, Ioanna (Department of Nursing, Faculty of Health Sciences, Cyprus University of Technology, 2018)
Background: “Health Care Professionals’ (HCPs’) compassion” rounds are a multidisciplinary forum aiming to help HCPs improve their emotional expression, teamwork and communication. The main aim of the study is to explore the perceptions and meanings of HCPs on “HCPs’ compassion” rounds and assess how these rounds impact to their teamwork and job satisfaction. Methods: A quasi experimental study with mix methodology was conducted in a cardiology/cardiosurgery hospital in Cyprus. Three rounds were conducted in which a patient case was described and then discussed by a multidisciplinary group. Twenty-five HCPs participated in the study who completed TeamSTEPPS (T-TPQ) and Minnesota Satisfaction Questionnaire “short form” (MSQ-short) validated in Greek, before and after the rounds. After the completion of the 3 rounds, 2 focus groups followed. Quantitative and qualitative data were analyzed using paired t-test and Colaizzi’s method, respectively. Results: Both teamwork (x̅before=87.12 vs x̅after=80.04, p=0.008) and job satisfaction (x̅before= 49.72 vs x̅after= 53.68, p=0.016) were found to be improved after the rounds. The core theme extracted by the qualitative analysis was “HPCs’ compassion rounds as a way of communication”. Overall, participants reported they were benefited by sharing concerns and identifying needs in their work environment. They also felt their teamwork was improved and the management that could be improved. Conclusions: The findings suggest that “HCPs’ compassion” rounds give the opportunity to HCPs to share concerns, queries and also identify their needs in their work environment. Moreover, they were found to contribute for more positive feelings about their colleagues.
Keywords: HCPs’ compassion rounds; Teamwork; Colaizzi’s method; Job satisfaction